2016
DOI: 10.2967/jnumed.115.167486
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of 18F-FDG PET/MRI and 18F-FDG PET/CT in Detection and Characterization of Pulmonary Lesions in 121 Oncologic Patients

Abstract: Our objective was to compare 18 F-FDG PET/MRI (performed using a contrast-enhanced T1-weighted fat-suppressed volume-interpolated breath-hold examination [VIBE]) with 18 F-FDG PET/CT for detecting and characterizing lung lesions in oncologic patients. Methods: In 121 oncologic patients with 241 lung lesions, PET/MRI was performed after PET/CT in a single-injection protocol (260 ± 58 MBq of 18 F-FDG). The detection rates were computed for MRI, the PET component of PET/CT, and the PET component of PET/MRI in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Another challenge in PET/MRI has been the detection of small pulmonary nodules. Recent studies have suggested that PET/MRI may fail to detect small pulmonary nodules (<5–10 mm) that are visible at PET/CT in oncology patients, potentially impacting treatment decisions . New approaches such as ultrashort echo time sequences (UTE) have been proposed to improve detection of pulmonary nodules measuring as small as 6 mm at MRI, but have yet to enter general clinical practice .…”
Section: Current Applications Of Pet/mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge in PET/MRI has been the detection of small pulmonary nodules. Recent studies have suggested that PET/MRI may fail to detect small pulmonary nodules (<5–10 mm) that are visible at PET/CT in oncology patients, potentially impacting treatment decisions . New approaches such as ultrashort echo time sequences (UTE) have been proposed to improve detection of pulmonary nodules measuring as small as 6 mm at MRI, but have yet to enter general clinical practice .…”
Section: Current Applications Of Pet/mrimentioning
confidence: 99%
“…Recent studies have suggested that PET/MRI may fail to detect small pulmonary nodules (<5-10 mm) that are visible at PET/CT in oncology patients, potentially impacting treatment decisions. [60][61][62] New approaches such as ultrashort echo time sequences (UTE) have been proposed to improve detection of pulmonary nodules measuring as small as 6 mm at MRI, but have yet to enter general clinical practice. 63 While detection of 6mm nodules may be sufficient for the stratification of bronchogenic carcinoma using Lung-RADS, 64 patients with other types of cancers may require evaluation and surveillance of even smaller nodules to discriminate benign nodules from early metastases, sometimes necessitating a dedicated inspiratory chest CT when PET/MRI or even PET/CT are performed.…”
Section: Current Applications Of Pet/mrimentioning
confidence: 99%
“…Wholebody MRI using these sequences can be used to identify signature patterns of muscular involvement in disorders such as facioscapulohumeral muscular dystrophy (FSHD). 17 Ongoing research has begun to incorporate more diverse imaging sequences, such as diffusion-weighted imaging, 18 contrast-enhanced imaging, 19 and positron emission tomography, 20 into whole-body MR imaging protocols.…”
Section: Whole-body Mrimentioning
confidence: 99%
“…MRI has an inferior spatial resolution to CT, which may reduce the detection of small pleural or pulmonary nodules [27]. Advances in PET/MRI image acquisition may help to overcome these difficulties.…”
Section: Discussionmentioning
confidence: 99%